2018
DOI: 10.1002/aur.1941
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of behavioral change in young adults with high‐functioning autism receiving virtual reality social cognition training: A pilot study

Abstract: Measuring treatment efficacy in individuals with Autism Spectrum Disorder (ASD) relies primarily on behaviors, with limited evidence as to the neural mechanisms underlying these behavioral gains. This pilot study addresses this void by investigating neural and behavioral changes in a Phase I trial in young adults with high‐functioning ASD who received an evidence‐based behavioral intervention, Virtual Reality‐Social Cognition Training over 5 weeks for a total of 10 hr. The participants were tested pre‐ and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 75 publications
(118 reference statements)
1
44
1
2
Order By: Relevance
“…If the reward system is selectively functioning in ASD, this system might be malleable, and behavioral intervention strategies that focus on social reinforcement might increase brain activity in response to social stimuli in this population. This hypothesis is supported by previous literature demonstrating neural changes in participants with ASD from pre- to post-intervention [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Increased Neural Reward Responsivity In Adolescents With supporting
confidence: 86%
“…If the reward system is selectively functioning in ASD, this system might be malleable, and behavioral intervention strategies that focus on social reinforcement might increase brain activity in response to social stimuli in this population. This hypothesis is supported by previous literature demonstrating neural changes in participants with ASD from pre- to post-intervention [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Increased Neural Reward Responsivity In Adolescents With supporting
confidence: 86%
“…Remotely-delivered, individualized coaching sessions with a trained coach helped participants understand and integrate this information. Our prior work has shown that cognitive strategy training can generalize beyond the trained domains to neural signatures underpinning brain health, such as increased brain blood flow, connectivity, and cortical thickness, with the brain changes linked to improved complex cognition, psychological well-being, real life functions, and social adeptness ( 31 , 32 , 48 52 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, VR has emerged as an engaging and effective tool for improving combined motor and cognitive performance. It is also possible that VR can help to teach more complex integrated cognitive/motor tasks such as those involving planning and executive functioning including bus‐taking, shopping and driving activities [Simoes, Bernardes, Barros, & Castelo‐Branco, ], and can also train social cognition as an essential component of these interactions [Yang et al, ]. Although, there are still some questions about whether the engagement in VR tasks is due to its novelty and motor interaction, studies highlight that motivation and attention are important features of VR systems (besides ease of use) which may contribute to increased interest and involvement in the tasks [Avola, Cinque, Foresti, & Marini, ; Osumi et al, ].…”
Section: Introductionmentioning
confidence: 99%